Exosomal long non-coding RNA LIPCAR derived from oxLDL-treated THP-1 cells regulates the proliferation of human umbilical vein endothelial cells and human vascular smooth muscle cells - Hu, Nan; Zeng, Xixi; Tang, Feifei; Xiong, Sizheng (Biochemical and biophysical research communications, 2021)
It has been reported that long non-coding RNA (lncRNA) LIPCAR is involved in the progression of atherosclerosis. However, the mechanism underlying the effects of LIPCAR on regulating the occurrence and development of atherosclerosis remains unclear. Reverse transcription-quantitative PCR was performed to detect the levels of LIPCAR in the plasma of patients with atherosclerosis and in THP-1 macrophages. THP-1 cells were stimulated with oxidized low-density lipoprotein (ox-LDL) to induce foam cell formation. Furthermore, Transwell assay was carried out to evaluate the migration ability of vascular smooth muscle cells (VSMCs). The expression of LIPCAR in the plasma of patients with atherosclerosis was significantly higher compared with that in healthy subjects, while LIPCAR knockdown notably reversed ox-LDL-induced THP-1 cell apoptosis. In addition, LIPCAR was upregulated in exosomes derived from THP-1 cells treated with ox-LDL (THP-1/ox-LDL Exo). Furthermore, THP-1/ox-LDL Exo significantly increased the expression levels of CDK2 and proliferative cell nuclear antigen in human VSMCs, while these effects were reversed following LIPCAR silencing. The results of the present study suggested that exosomal lncRNA LIPCAR derived from ox-LDL modified THP-1 cells could promote the progression of atherosclerosis. Therefore, LIPCAR may be considered as a novel biomarker for the development of new strategies to treat atherosclerosis. •The level of Long non-coding RNAs (lncRNA) LIPCAR was upregulated in exosomes derived from THP-1 cells that were treated with oxidized low density lipoprotein (oxLDL).•THP-1/oxLDL Exo reduced the viability of human umbilical vein endothelial cells by inducing apoptosis; however, these phenomena were reversed by LIPCAR knockdown.•THP-1/oxLDL Exo obviously upregulated the levels of CDK2 and PCNA in human vascular smooth muscle cells (VSMCs).